Differential contribution of interleukin‐10 promoter variants in malaria and schistosomiasis mono‐ and co‐infections among Nigerian children. Issue 1 (24th November 2017) - Adedoja, Ayodele; Hoan, Nghiem Xuan; van Tong, Hoang; Adukpo, Selorme; Tijani, Deborah B.; Akanbi, Ajibola A.; Meyer, Christian G.; Ojurongbe, Olusola; Velavan, Thirumalaisamy P.
Abstract: Objective: Interleukin‐10 (IL‐10) is an anti‐inflammatory cytokine produced by Th1 cells and macrophages. The rationale of this study was to examine and validate possible contributions of IL‐10 promoter polymorphisms in sub‐Saharan Africa in children infected with either Plasmodium falciparum or Schistosoma haematobium and in children co‐infected with both parasites. Materials and Methods: A total of 309 Nigerian children aged 4–15 years were recruited. The study group consisted of individuals infected either with P. falciparum ( n = 76) or S. haematobium ( n = 94) in mono‐infections, a group of children co‐infected with both P. falciparum and S. haematobium ( n = 62) and matched healthy controls ( n = 77). The IL‐10 promoter polymorphisms ‐1082G/A, ‐819C/T and ‐592C/A were genotyped by direct sequencing. Results: The frequencies of the IL‐10 ‐1082GG genotype, the ‐1082G allele and haplotype GCC (positions ‐1082, ‐819 and ‐592) were higher in children infected with P. falciparum than in healthy controls, indicating that the ‐1082GG genotype and the ‐1082G allele and the GCC haplotype are associated with increased susceptibility to malaria infection (OR = 3.4, 95% CI = 1.2–10.8, P = 0.02; OR = 2.5, 95% CI = 1.1–3.4, P = 0.02; OR = 3.8, 95% CI = 2.0–7.2, P = 0.0001, respectively). Children with the ‐ 1082GG genotype had a higher parasitaemia than children with the ‐1082AA or ‐1082AG genotypes ( P = 0.0017). Haplotype GCC occurred more frequently in children infected with S. haematobium, while haplotype GTA was less frequent than in controls (OR = 2.2, 95% CI = 1.2–4.4, P = 0.017 and OR = 0.1, 95% CI = 0.02–0.5, P = 0.0004, respectively). No differences in the frequencies of IL‐10 promoter polymorphisms were observed between children with P. falciparum – S. haematobium co‐infections and healthy controls. Conclusion: Although IL‐10 promoter polymorphisms are not associated with P. falciparum and S. haematobium co‐infection, variant ‐1082G/A and haplotype GCC are associated with malaria, whereas the IL‐10 haplotypes GCC and GTA are associated with schistosomiasis.